Development of an Automatic Clothesline System Based on Weather Sensors and Telegram Notification - Hanifan Budi Kustiawan; Heri Sudibyo; Dwi Winarti (bit-Tech, 2025)
Unpredictable weather conditions often cause outdoor laundry to become wet again, requiring constant manual monitoring. This study presents the design and development of an Internet of Things (IoT)-based automatic clothes drying system that responds to real-time environmental changes and offers remote control via the Telegram application. The system employs an ESP32 microcontroller integrated with a rain sensor, a DHT22 humidity sensor, and an LDR light sensor. Sensor data is processed in real time using predefined threshold values: when rain is detected, humidity exceeds 26%, or light intensity rises above 3500 lux, the ESP32 triggers a servo motor to retract the clothesline. Conversely, in dry and bright conditions (humidity < 25%, light < 3400 lux), the system extends the clothesline. A servo motor is used as the actuator to retract or extend the drying rack. A Telegram Bot is also integrated to deliver real-time notifications and accept manual commands such as /masuk, /keluar, and /status. The development method follows a prototyping approach that includes requirement analysis, hardware-software integration, and system evaluation. Experimental results show that the system achieved over 95% accuracy in detecting environmental changes and responded within 2–3 seconds to commands and sensor triggers. The combination of sensor automation and interactive Telegram control demonstrates reliability and flexibility in smart-home applications. In conclusion, the proposed system provides an effective and user-friendly solution for managing outdoor laundry in variable weather conditions, with promising potential for future enhancements in IoT-based household automation.